Dry Deposition Techniques for Biobased Diabetic Inhibitor - Jaya, Mohd Rafaei (Universiti Teknologi PETRONAS, 2016)
Despite the numerous preventative strategies and armories of medication, the management of diabetes remains grossly unsatisfactory. In Malaysia, diabetes is emerging as a pandemic and has been shown to be closely related to increased premature and preventable mortality, as well as macro and microvascular complications such as heart disease, stroke, end-stage renal failure, blindness and amputation. The burden of diabetes continues to increase in Malaysia. Therefore, it is important to identify novel nutraceuticals or drugs for curing or preventing diabetes, which have fewer side effects. Many biochemists have found that natural compounds especially chitosan, phenolic compounds and beta-glucans as biocompatible, biodegradable and non-toxic which made wide applicability in conventional pharmaceutics as a potential formulation excipient (Przekora et al., 2014).